Collaboration and the academic library : internal and external, local and regional, national and international - Atkinson, P. J. (United Kingdom Elsevier, 2018)
"Collaboration and the Academic Library: Internal and External, Local and Regional, National and International explores the considerable change that has affected universities and academic libraries in recent years. Given this complex and important context, it is clear that the academic library increasingly needs to operate in partnership with its users and other professionals and organizations to be successful in meeting the needs of its clientele. Academic librarians need to work closely with client groups so that services are relevant, and close partnerships with other professionals need to be forged to provide seamless services for users. The book looks at all aspects of collaboration affecting academic libraries, both internally and externally, to help the reader understand future directions for collaborative activities in a complex and difficult working environment.Considers collaboration issues affecting academic libraries. Covers both internal and external collaboration. Provides readers with direction for collaborative activities. Shows how academic librarians can work with client groups to keep services relevant"--
Includes bibliographical references and index.
"Further reading": pages 233-240.
Keywords: Academic libraries; Communication in learning and scholarship; Library cooperation; Library cooperation -- Case studies; Academic libraries; Library cooperation